2023
DOI: 10.3390/su15032466
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation and Technological Innovation on Higher Education Post-COVID-19

Abstract: The university is an important pillar in sustainable development; however, COVID-19 imposed new dynamics that called for rethinking university praxis to achieve this mission, and although the systematization of good practices is a powerful mechanism for understanding educational success, this perspective of positive change has been little developed. Hence, the present study aimed to identify positive cores of faculty in their successful post-COVID-19 performance. A qualitative methodological approach was deplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Moreover, remote work offers flexibility, reducing work-family conflicts and improving family relationships [ 35 , 36 ]. It also allows for increased time for leisure and exercise, which positively impacts both physical and mental health and increases work productivity [ 37 ]. In addition to the benefits for employees, remote work has environ-mental advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, remote work offers flexibility, reducing work-family conflicts and improving family relationships [ 35 , 36 ]. It also allows for increased time for leisure and exercise, which positively impacts both physical and mental health and increases work productivity [ 37 ]. In addition to the benefits for employees, remote work has environ-mental advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Este modelo se basa en gran medida en la confianza en el papel profesional de los educadores (Chan, 2023). Las demandas de la era digital se aplican tanto a los estudiantes, que son la próxima generación de la fuerza laboral, como a los docentes, que son facilitadores del modelo de competencias (Deroncele-Acosta et al, 2023). Volumen 5 N°4.…”
Section: Conclusiónunclassified
“…La pandemia de coronavirus ha obligado a millones de estudiantes a realizar cursos en línea en un experimento de aprendizaje global sin precedentes (Deroncele-Acosta et al, 2023). Este cambio repentino ha llevado a un aumento significativo de las habilidades digitales de la educación superior profesional.…”
Section: Artículo Originalunclassified
“…The global socio-educational context is experiencing the post-pandemic period which has accelerated the processes of digital transformation and technological innovation in education [21]. Thus, with the advancement of the computerization of education, educational management methods have gradually become more information-based and large amounts of data stored in teaching have accumulated [70], calling for educational innovation with ICT to promote relevant learning [60], which necessarily requires digital competencies.…”
Section: Educational Innovation and Ictmentioning
confidence: 99%
“…This cannot be achieved today outside of a single discipline, as it requires multidisciplinary collaboration and interdisciplinary approaches as a model of sustainable research [2], nor can it be achieved outside of technology, especially when it has been demonstrated how digital transformation can contribute to sustainability in HEIs [20]. In this regard, a recent study showed important findings for the future of higher education based on digital transformation and technological innovation [21].…”
Section: Introductionmentioning
confidence: 99%